2021
DOI: 10.3389/fmed.2021.671215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen: A Promising Adjunctive Strategy for the Treatment of the COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has no specific and effective treatment. The pathophysiological process of the COVID-19 is an excessive inflammatory response after an organism infects with a virus. Inflammatory storms play an important role in the development of the COVID-19. A large number of studies have confirmed that hydrogen has a therapeutic effect on many diseases via inhibiting excessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The clinical and biological observations of our study are consistent with the literature, considering that H 2 has been described as able to reduce lung injury and thus to reduce the number of critically ill patients [31]. Another literature review has explained that H 2 could directly enter the lung tissue through ventilatory activities and exert anti-inflammatory effects at the multiple stages of the inflammatory response, alleviating the airway damage caused by the excessive activation of the inflammatory cells and the massive release of inflammatory factors [32]. In addition, during Covid-19 associated pulmonary injury, activation of resident alveolar macrophages has led to the release of potent proinflammatory mediators and chemokines that promote the accumulation of neutrophils and monocytes [33].…”
Section: Discussionsupporting
confidence: 92%
“…The clinical and biological observations of our study are consistent with the literature, considering that H 2 has been described as able to reduce lung injury and thus to reduce the number of critically ill patients [31]. Another literature review has explained that H 2 could directly enter the lung tissue through ventilatory activities and exert anti-inflammatory effects at the multiple stages of the inflammatory response, alleviating the airway damage caused by the excessive activation of the inflammatory cells and the massive release of inflammatory factors [32]. In addition, during Covid-19 associated pulmonary injury, activation of resident alveolar macrophages has led to the release of potent proinflammatory mediators and chemokines that promote the accumulation of neutrophils and monocytes [33].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have indicated that H 2 has anti-inflammatory [ 22 ], anti-apoptosis [ 23 ], antifatigue [ 24 , 25 , 26 , 27 ], and regulatory properties [ 28 ]. Based on the reported beneficial health effects across a variety of diagnoses [ 22 , 29 ], H 2 administration has recently been proposed as a promising therapeutic gas for COVID-19 patients [ 7 , 30 , 31 , 32 , 33 , 34 , 35 ]. For instance, Guan et al [ 36 ] showed clinically beneficial effects of a hydrogen/oxygen (H 2 –O 2 ; 66–33%) mixed gas inhalation for the amelioration of most respiratory symptoms, such as dyspnea, chest distress, or cough, within days 2 and 3 of hospitalization for COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although approximately 80% of people who contracted COVID-19 in the first instance were asymptomatic, or experienced mild flu-like symptoms, 4 the initial wave of disease caused a significant burden for healthcare industries as 15% of patients required nosocomial care, and a further 5% needing critical ministrations. 5 Considering patient well-being and the impact this has on global socioeconomic factors, a report commissioned by the WHO in February of 2020 declared the median time for clinical recovery in mild cases of COVID-19 was 14 days, whilst analysis of recovery rates in severe or critical illness found 21-42 days were more typical. 6 In symptomatic patients, COVID-19 typically presents with episodes of continuous, non-productive coughing, fever, a loss of olfactory and gustatory senses, and musculoskeletal and respiratory distress.…”
Section: Introductionmentioning
confidence: 99%